2017
DOI: 10.1016/j.jinorgbio.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

New 4′-(4-chlorophenyl)-2,2′:6′,2″-terpyridine ruthenium(II) complexes: Synthesis, characterization, interaction with DNA/BSA and cytotoxicity studies

Abstract: In this study, we have developed a series of new monofunctional Ru(II) complexes of the general formula mer-[Ru(Cl-Ph-tpy)(N-N)Cl]Cl in which Cl-Ph-tpy is 4'-(4-chlorophenyl)-2,2':6',2″-terpyridine, N-N is a bidentate chelating ligand (1,2-diaminoethane (en, 1), 1,2-diaminocyclohexane (dach, 2) or 2,2'-bipyridine (bpy, 3)). All complexes were fully characterized by elemental analysis and spectroscopic techniques (IR, UV-Vis, 1D and 2D NMR). Their chemical behavior in aqueous solution was studied by UV-Vis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…erefore, the studies aimed at the binding of biologically active compounds with this protein provide useful information on their biodistribution, toxicity, and mechanism of action [52]. Bovine serum albumin (BSA) represents the structural analog of the human serum albumin (HSA) and is the most extensively studied serum albumin for metal complexes interactions [53]. It contains three fluorophores, namely, tryptophan, tyrosine, and phenylalanine; nevertheless, the intrinsic fluorescence of BSA is mainly due to tryptophan alone [54].…”
Section: Bsa Interactionsmentioning
confidence: 99%
“…erefore, the studies aimed at the binding of biologically active compounds with this protein provide useful information on their biodistribution, toxicity, and mechanism of action [52]. Bovine serum albumin (BSA) represents the structural analog of the human serum albumin (HSA) and is the most extensively studied serum albumin for metal complexes interactions [53]. It contains three fluorophores, namely, tryptophan, tyrosine, and phenylalanine; nevertheless, the intrinsic fluorescence of BSA is mainly due to tryptophan alone [54].…”
Section: Bsa Interactionsmentioning
confidence: 99%
“…All the complexes showed significant antibacterial activities against all the tested bacteria [41]. These results suggested that the cytotoxicity depends upon the nature of bidentate and tridentate ligand coordinated to the metal center [42]. Fig.…”
Section: H Nmr Spectramentioning
confidence: 73%
“…The above‐observed phenomenon may be due to the changes in protein tertiary structure that make some changes environment of tryptophan of BSA, thus indicating the interactions of complexes C1 and C2 to the albumin . The redshift infers the formation of the metal complex‐ BSA adducts, which changed the polarity of the microenvironment in the locality of tryptophan …”
Section: Resultsmentioning
confidence: 99%